Identification factor of constraint in road construction in Sabah - Nur Atika, Abd Rahman (2019)
Constraint in road construction can be defined as anything that limits an organization or entity from moving toward or achieving its goal to accomplish the project. Constraints in a multi-party working situation bring complications in road construction project management. These can further develop into conflicts and disputes, which bring cost consequences, direct and indirect, to clients and contractor (Yates, 2002). It is important to identify the potential constraints in the construction project, which will help to decrease the unnecessary wastage and loss of both money and time because of inadequate planning. Therefore, the main goal of this study was to identify the factor of constraint in road construction. This study carried out based on literature review and questionnaire survey. A total of five categories were contributed to the main factor of constraint in road construction was identified based on literature review. A questionnaire survey was distributed to the randomly respondent in Sabah. The target respondent of questionnaire are developer, consultant, contractor, engineer and project manager. The top three most important factors that contributed to constraint in road construction were budget limit and allocation of the money for the construction not enough, poor company management, and price fluctuation. Social constraint and economic constraint were ranked the main categories of constraint in road construction, followed by legal constraint, technical constraint and environmental constraint.